Narrative Competence on Nationalism - Zaman, Zufar Arsyad; Davids, Mogamat Noor (Universitas Negeri Semarang, 2024)
This research aims to analyze narrative competence on nationalism. This research uses qualitative research methods with a descriptive approach. This research was carried out at SMA Muhammadiyah 2 Semarang (a Senior High School) with class XI history teachers and several class XI students as informants. The data collection techniques used in this research are in-depth interviews, observation, and document review. Test the validity of the data using source triangulation and technical triangulation. The research results show; students have implemented the material on the history of the proclamation, however some students do not really know in depth about the events of the proclamation. Students feel happy in learning about the history of the Indonesian proclamation material. Students have shown nationalist attitudes at school and in everyday life, but there are students who feel that nationalist attitudes are normal. This research has limitations, namely the analysis at a single research location. The results of this research encourage future researchers to continue research on a broader scope.